«Nationalists» and «right opportunists» arraigned in Kazakhstan (Journal of history, 2019)
This article deals with the tragedy that brought Goloshchekin, and the policy «small October» that caused the genocide in Kazakhstan in 2030 years of the XX century. The first step towards the establishment of revolutions in the Kazakh steppe, which brought great famine in our land, was forced by establishing nomadic people. Mass collectivization of the peasants in Kazakhstan was forced by establishing nomadic and seminomadic people.In their tentative to make the category establishing of nomadic and seminomadic people, members of the party banished the rich nomads. Those who had offered other ways were «opportunists» and «legals». Higher intelligentsia of Kazakh people and members of the «Alash» motion that had offered connecting of nomadic people not in class,instead at the national level, were ruthlessly persecuted by members of the StalinistGoloschekinist machine. This article refers to the «nationalists» and «opportunists» who were injured by the bloody noose of Goloshekin.